(untitled) - Richardson, Gary L. (Boston, Mass, 2006)
Introducing the first collection of IT Project Management readings in the academic market! Readings in Information Technology Project Management provides users with real-world examples of information project management from experienced project managers. Comprehensive case studies coupled with various perspectives from experienced project managers are sure to equip users with a strong foundation for success in today’s business world.
Keywords: Project management,Information technology,Quản lý đề án,Công nghệ thông tin; Management,Quản lý